Organizacja jako system otwarty i dynamiczny - Grzybowska, Katarzyna (An organization as an open and dynamic system, 2006)
The contents of the article refers the conception of the theory of open and dynamic systems. In the organizations there is not only production of entropy resulting from irreversible processes, but also its inflow which can be also negative. This happens in the case of a living organism which "imports" complex molecules which are rich in free energy. Therefore, living systems, being in stability, can avoid the increase of entropy and can even develop in the direction of an increased order and organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 90-96